On emergent complex behaviour, self-organised criticality and phase transitions in multi-agent systems: autonomy oriented computing (AOC) perspectives. (12th May 2008) - Liu, Jiming; Hu, Bingcheng
In a Multi-Agent System (MAS), there usually exist system-level goals that agents are collectively trying to attain. Generally speaking, the local behaviours and performances of individual agents directly determine which global characteristics of an MAS, for example, the global performance and/or patterns, will emerge and how the system-level goals will be attained. In most cases, such a local?global relationship is neither obvious nor straightforward. In this paper, we will address several issues on modelling emergent complex behaviours in MAS. In particular, we will focus on the local?global relationship in a Self-Organising MAS (SOMAS), and discuss the phenomena of Self-Organised Criticality (SOC) and phase transition in SOMAS.